Ethics, Governance and Risk Management in Organizations - Saidon, Intan Marzita; Said, Roshima (Accounting, Finance, Sustainability, Governance & Fraud: Theory and Application, 2020)
XX, 179 p. 14 illus., 9 illus. in color.